2019
DOI: 10.5194/hess-23-2763-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sediment budget analysis of the Guayas River using a process-based model

Abstract: Abstract. The equatorial Daule and Babahoyo rivers meet and combine into the tidal Guayas River, which flows into the largest estuary on the Pacific coast of South America. The city of Guayaquil, located along the Guayas, is the main port of Ecuador but, at the same time, the planet's fourth most vulnerable city to future flooding due to climate change. Sedimentation, which has increased in recent years, is seen as one of the factors contributing to the risk of flooding. The cause of this sedimentation is the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…Upstream erosion lowers water quality and leads to siltation and associated flooding downstream (Barrowclough et al, 2016;Barrera Crespo et al, 2019;Restrepo & Escobar, 2018;Rosas et al, 2020). Climate change will not only affect the sustainability of soils in the higher elevations but will also impact lower elevation areas, where siltations will reduce water storage and create greater potential for flooding (Barrera Crespo et al, 2019).…”
Section: Soil Erosion and Its Environmental And Economic Impacts On The Andean Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upstream erosion lowers water quality and leads to siltation and associated flooding downstream (Barrowclough et al, 2016;Barrera Crespo et al, 2019;Restrepo & Escobar, 2018;Rosas et al, 2020). Climate change will not only affect the sustainability of soils in the higher elevations but will also impact lower elevation areas, where siltations will reduce water storage and create greater potential for flooding (Barrera Crespo et al, 2019).…”
Section: Soil Erosion and Its Environmental And Economic Impacts On The Andean Regionmentioning
confidence: 99%
“…), so they have to be established off-season (Alwang et al, 2013). Delgado et al (2019) and Barrera et al (2019) found that there was enough moisture for the establishment of an oat (Avena sativa L.)-vetch (Vicia sativa L.) mix planted right after harvest of the cash crop. Alwang et al (2013) found that more than 30% of the cover crops in CA trials could not be established without supplementary water after the cash crop was harvested.…”
Section: Potential To Use Soil and Water Conservation For Climate Change Adaptation In The Regionmentioning
confidence: 99%
“…The second, the coastal region, is a region of high aggressiveness, with greater erosive potential and sedimentation problems in the lower part of the basin due to the erosive capacity of rainfall [40]. The Guayas River basin has been affected by extreme phenomena such as El Niño [41], which caused flooding in 1965, 1972, 1973, 1976, 1983, 1987, 1992 and 1998 [36,39,42], and La Niña [43]. The lower part of the basin has greater exposure to flooding [44].…”
Section: Study Areamentioning
confidence: 99%
“…This package can handle dynamic 10.1029/2020WR027544 interactions of storm surge, hurricanes, and tsunamis and provide detailed information of water level, flow rates, and velocity (Deltares, 2019a). Furthermore, this package has been widely used in similar compound flooding and river discharge-tide interaction studies (Barrera et al, 2019;Kumbier et al, 2018;Muñoz et al, 2020), and salt marsh research (Fagherazzi et al, 2014;Marciano et al, 2005) including intertidal creeks and overmarsh circulation analyses in Savannah's wetlands with satisfactory results (Sullivan et al, 2015(Sullivan et al, , 2019.…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
“…Bottom friction coefficients associated with the Atlantic Ocean and river bed are calibrated recursively in order to replicate the observed total water levels from USGS and NOAA stations with high accuracy. We use spatially varying bed roughness values in the Savannah model to account for anthropogenic interventions (e.g., dredged river channel, Figure 2b), heterogeneities in river morphology, and sediment deposition patterns within fluvial to tidal transition zones (Barrera et al, 2019;Hoitink et al, 2017;Kästner et al, 2017). The calibrated Manning's coefficient values in the model domain are n = 0.018 (Atlantic Ocean), n = 0.042 (dredged channel), and n = 0.035 (upstream part or the river).…”
Section: Model Calibrationmentioning
confidence: 99%